Talent Management: Three new Perceptions intended for managing and retaining Talent in Bangladesh - Mohaimen, Md. Abul (Asian Business Review, 2013)
This study aims at investigating the methods, importance, process, and present situation of managing talented employees in Corporations. The study revealed that having talented employees helps organizations to drive and be competitive but it is difficult to acquire such people. Thus, some innovative campaigns, for instance, global trainee and management cycle star programs have been created to motivate talented graduates to join the companies and to motivate existing talented employees to being more dedicated and engaged. In the recruitment of new employees, personality and interpersonal skills were more important than educational background because candidates were deemed to be proficient in specific areas, so, what a candidate must have is a personality matching the company’s culture especially the characteristic of working as a good team member. In this study, we suggested some important steps and methods that can be applied in the organizations which are totally running and managing by the HR Department. Moreover, these methods and steps can become successful by managing low rate of star turnover which is quite sensitive case now a day. JEL Classification Code: J24